The integration of affective characteristics of the family environment for a more comprehensive explanatory model of reading abilities - Gagné, Andréanne; Bigras, Nathalie; Charron, Annie; Lemire, Julie (Frontiers in Education, 2022)
This research focuses on the influence of familial affective characteristics on family literacy practices and children’s reading abilities. Parenting stress and educational practices were two affective characteristics of interest considering the pandemic context. Parenting stress is defined as a state of psychological discomfort specifically associated with the education of a child whereas educational practices are defined as various means the parent uses to educate and socialize the child. A sample of 154 grade 1 children allowed for a correlational analysis between parenting stress, educational practices, the frequency of family reading activities, the diversity of literacy material available and the type of child-parent exchange (alphabet-focus or story-focus). Regression analyses were conducted to develop a model predicting reading abilities. Three result outcomes are of interest for the field of reading development. First, our study establishes relations between educational practices and certain aspects of family literacy: diversity of supports, frequency of exchanges, and type of child-parent exchange and it suggests that parental engagement plays a significant role in various aspects related to at-home discussions about books. Second, our regression analysis highlights evidence that parenting stress is an explanatory factor directly linked to the child’s reading abilities. Therefore, our findings add reading abilities to the list of developmental aspects that is affected by parenting stress. Finally, the results show that, when parenting stress and educational practices are integrated in the predictive model, the story-focus exchanges remain predictive of reading abilities but not the alphabet-focus exchanges. Hence, our findings confirm that the benefit of parent-child exchange on reading abilities is dependent of conditions of the family environment in which these activities occur. These findings also lead us to question the value of making alphabet-focus exchanges, the cornerstone of some literacy programs in family settings. Our findings call for caution when implementing such programs in family context. In fact, activities involving conversation about the meaning of a text or the links between the text and the child’s everyday reality represent the only activities, in our study, that had a beneficial effect on reading abilities while remaining permeable to parenting stress.